Improvement of Absorption and Emission Phenomena of 1.55µm Quantum Dot Laser using Indium Nitride - Humayun, Md. Abdullah Al; Rashid, Mohd Abdur; Kuwana, Anna; Kobayashi, Haruo (Engineering, Technology & Applied Science Research, 2023)
This paper presents the improvement of emission and absorption phenomena of 1.55µm quantum dot laser by enhancing the stability of oscillation frequency and minimizing absorption loss. Among the key parameters related to these absorption and emission phenomena, the effective density of state, rate of change of carrier mobility, and optical feedback level were extensively investigated to reduce the fluctuation of the oscillation frequency of the emitted light as well as the absorption loss. These phenomena were investigated through mathematical analysis and numerical simulation using AlN, GaN, and InN quantum dots as the active material of the laser structure. The numerical results were compared, confirming that the InN quantum dot in the active layer significantly improved the absorption and emission phenomena of the quantum dot laser. At the same time, InN is capable of emitting light at a wavelength of 1.55µm due to its band gap of 0.7eV. Consequently, InN has a superior potentiality to other existing materials to fabricate the quantum dot laser operating at the 1.55µm wavelength, which is the window of an optical fiber communication system that offers the lowest attenuation. Therefore, the InN quantum dot laser is expected to be a promising candidate not only in the field of semiconductor technology but also in the field of optical communication in the imminent future.